RANDOMIZED CLINICAL TRIAL OF OMEPRAZOLE AND RANITIDINE USING INDONESIAN TRANSLATED NEPEAN DYSPEPSIA INDEX - Arinton, I Gede; Samudro, Pugud; Sutrisna, Eman; IDN, Wibawa (journal of internal medicine; Vol. 7, No. 3 September 2006, 2012)
In patients with dyspepsia, a common initial management strategy in primary care is to prescribe a course of empiric antisecretory therapy. Ranitidin and omeprazole as antisecretory agents have been proven effective for treatment of dyspepsia. This research was aimed to evaluate the effect of omeprazole and ranitidine by using Nepean Dyspepsia Index (NDI) which was translated and validated in Indonesian language. Fifty healthy persons were asked to complete the Indonesia translated NDI(NDII) and Short Form(SF)- 36, which was previously validated. Cronbach' s alpha and test-retest were performed for reliability analysis. Spearman's rank correlation was used to assess validity. P -value <0.03 was considered statistically significant. The results concluded that NDIl can be used in dyspepsia patients who understand Indonesian language. The number of 104 subjects with a clinical diagnosis of dyspepsia according to the inclusion and exclusion criteria were recruited and randomized to receive ranitidine 150 mg twice daily and omeprazole 20 mg twice daily. Symptoms of dyspepsia were evaluated by using NDIl at baseline one week after treatment. The outcomes of omeprazole and ranitidine were evaluated by comparing improved NDIl score in 5 domains (tension, activities, eating/drinking, knowledge/control and work/study). The mean of age in the subjects was 47 years old that consisted of 36% male. After one week treatment, the NDIl dyspepsia patients score in omeprazole treated group was not significantly different from that in ranitidine treated group. The effect of omeprazole was not better than ranitidine when it was given as empirical treatment for dyspepsia patients in primary care.
Keywords: randomized clinical trial, dyspepsia, NDI, NDIl, omeprazole, ranitidine.